PERSEPSI DIRI TERHADAP KEMAMPUAN BERBAHASA MAHASISWA BAHASA INGGRIS - Ihda Husnayaini (Scientia: Jurnal Hasil Penelitian, 2016)
The purpose of this study is to determine (1) self-perception of students toward English language skills, and (2) differences in perception of language skills among female students and male students. Population and sample of this research is the students of the first semester of the English study program STAIN Syaikh Abdurrahman Siddik Babel. The research data was collected by distributing questionnaires of self-perception of English ability. The data were analyzed by finding the average value and the percentage of self-perception of students, consisting of two parts of the statement, which included an assessment of the ability of themselves and their affective aspects. The results show that most of the research subjects have a fairly positive self-perception about their English language skills, especially in pronouncing simple things in English. Moreover, in general, they have a pretty good ability in the affective aspects of learning English. But overall, male students have a more positive self-perception, both in terms of ability to practice English or in the affective aspects when studying English in the classroom than female students. This could indicate that the average proficiency of male students are better than female students because, based on many previous studies, self-perception can be a reflection of the actual individual condition.